2021
DOI: 10.3389/froh.2021.740469
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oral Squamous Cell Carcinoma Associated Inflammation: A Pilot Study

Abstract: Background: Oral squamous cell carcinoma (OSCC) is a devastating disease that is usually associated with a dense associated inflammatory infiltrate. Characterizing tumor-associated inflammation is critical to understand the pathogenies of tumor development and progression.Methods: We have tested a protocol to analyze tissue and salivary immune cells and mediators of 37 patients with OSCC at different stages and compared to eight chronic periodontitis patients and 24 healthy controls. Tissue analysis was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Our data are in concordance with previous reports detecting higher levels of IL10, IP-10 (CXCL10), and IL-8 in peripheral blood of HNSCC compared to HD ( 7 – 9 ). Yet, the HIS stratification model illustrated in the current work revealed differential expression of IL10 in the HIS-INF, and IP-10, and IL8 in HIS-IE compared to HD.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in concordance with previous reports detecting higher levels of IL10, IP-10 (CXCL10), and IL-8 in peripheral blood of HNSCC compared to HD ( 7 – 9 ). Yet, the HIS stratification model illustrated in the current work revealed differential expression of IL10 in the HIS-INF, and IP-10, and IL8 in HIS-IE compared to HD.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, despite the questionable relationship between chronic in ammation and carcinogenesis, recent studies suggest that it could promote genetic and epigenetic changes that might lead to the development of oral SCC. [30][31][32] The presence of epithelial dysplasia is reported in the literature in 0.5-25% of OLP cases 12,21,33,34 and 5.6-27.2% of LLO cases. 21,33 Concerning the degree of epithelial dysplasia, Vijayan and Muthukrishnan 35 in 2022 found that out of 250 OLP lesions, 14 (5.6%) exhibited epithelial dysplasia, with 12 having mild epithelial dysplasia and 2 moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that there is a significant pro-inflammatory immune environment in OSCC. [17] In the tumor microenvironment, the production of a variety of pro-inflammatory cytokines can promote the survival and proliferation of tumor cells. [18,19] CDSN is located in the core of desmosomes in the cuticle.…”
Section: Discussionmentioning
confidence: 99%